Asuhan Keperawatan pada Pasien Pre Operasi Prostatektomi dengan Masalah Keperawatan Ansietas Menggunakan Teknik Relaksasi Nafas Dalam dan Distraksi Lima Jari - Berticarahmi Berticarahmi; Pujiarto Pujiarto (Jurnal Kesehatan Panca Bhakti Lampung, 2019)
In patients with pre-surgery, especially pre-prostatectomy, anxiety or anxiety usually arises such as difficulty sleeping, arrhythmia, discomfort, excessive worry and panic. Anxiety needs attention and nursing intervention because of the emotional state of the patient which will affect the patient's body function before the surgery. High anxiety can have an effect on affecting the physiological functions of the body. Deep breath relaxation and five-finger distraction are two therapies that can be combined to overcome anxiety problems in preoperative patients. The purpose of this study was to determine the effect of giving deep breath therapy and five finger distraction in patients pre prostatectomy with anxiety or anxiety problems. This type of research is descriptive using the case study approach method. This study was conducted with two respondents pre prostatectomy with anxiety problems. Based on the results of the study it was found that deep breath relaxation therapy and five-finger distraction can reduce anxiety in patients pre prostatectomy surgery. It is expected that deep breath relaxation and five-finger distraction studies in preoperative patients with anxiety problems can help various parties in resolving anxiety problems in patients pre prostatectomy surgery.